Increasing fatigue crack initiation life in butt-welded UIC60 rail by optimization of welding process parameters - Ghazanfari, Mohsen; Hosseini Tehrani, Parisa (International journal of fatigue, 2021)
•A thermal-metallurgical-mechanical coupled FEM is used to estimate the fatigue life and crack initiation angle in the welded rails based on the critical plane method.•The predicted crack initiation angle is verified by comparing it with the failed butt-welded rail in the Iranian railway networks.•Optimization of FBW with the aim of fatigue life increasing is performed.•87% increase in crack initiation life is achieved by optimization of the FBW process. In this work, to reduce the fracture in butt-welded rail under service loads, a numerical study is carried out to estimate the crack initiation life. For this purpose, the J-S model in terms of the critical plane method is used. To increase the fatigue life of the welded joint, considering the amount of fractured butt welded joints in the railway of the Iranian network, the important variables of the flash-butt welding process are optimized. To this end, the welding process modeling in Abaqus is converted to Python code, and by using a coupled procedure utilizing Matlab, the optimization process is performed by the imperialist competitive algorithm (ICA). The capability of each governing variable on increasing crack initiation life is discussed.